Factores de riesgo psicosocial que afectan a los profesionales en enfermería - Orozco-Vásquez, Margarita-María; Zuluaga-Ramírez, Yury-Carolina; Pulido-Bello, Geraldine (Revista Colombiana de Enfermería, 2019)
Objective: Review the scientific evidence on psychosocial risk factors: quantitative, work rate, double presence and emotional demands on nursing professionals in healthcare services. Material and method: A review of scientific articles was carried out from 2007 to 2018 in Medline, PubMed, ScienceDirect, Scopus, OVID Nursing, Springer, Taylor and Francis and other electronic databases such as SciELO and Lilacs, through the descriptors: nursing, occupational health, working conditions, work stress, and workload. We selected 74 articles that met the inclusion criteria. Results: Quantitative demands and the intensification of the rhythm of work increase the nurse’s work overload due large quantity of patients and functions unrelated to the exercise of direct care. The emotional demands originate during caretaking actions and in the permanent confrontation with suffering, pain and death. The combination of salaried and domestic work, as well as undertaking two or more jobs and shift work, are frequent aspects in nursing professionals. Conclusion: The nursing professional is exposed to psychosocial risk factors: quantitative, work pace, double presence and emotional demands, which can negatively affect their physical and mental health, as well as the quality of the care provided.